Security Agencies and Human Right Violations in Nigeria - Matthew Funsho Bello; Keneth Mela (JPAS (Journal of Public Administration Studies), 2023)
It is no news that Nigeria, which is arguably the giant of Africa, is known for human rights violations. From its years of military authoritarianism which witnessed the killing of several human rights activists, and since the return to democratic rule, the country’s human rights narrative has not changed. Government authorities and law enforcement agents (the police) frequently engage in various human rights violations, notably unlawful killings, torture, ill-treatment of no crime suspects, forced evictions, interference with the rights to peaceful assembly and freedom of association, and violence against women and children are widespread across the country. This has created worrisome threats to lives and government seems to be grappling with the situation, hence there is some measure of friction between the activities of security agencies and human right in Nigeria. It is against this backdrop that pertinent questions are asked on how well security agencies could be operated without infringement on fundamental human rights and what are the probable mechanisms that could be adopted by security agencies without abuse of human rights in Nigeria. Answers to these questions instigated this research work. This study exemplified the extent of human rights abuses in Nigerian democratic governance. It equally highlighted causes and the effects of human rights abuses in Nigeria and made recommendations on how to prevent its occurrences in the future. Secondary sources of data thus become the hub of its methodology. The study adopted system theory by Gabriel Almond as its theoretical framework.